Specification for power-driven mobile cranes (BSI, 1986)
Mobile cranes, Cranes, Jib cranes, Lifting equipment, Commercial road vehicles, Road vehicle components, Marking, Structural design, Design, Stability, Joints, Wire ropes, Steel-wire ropes, Hoisting drums, Lifting tackle, Pulleys, Brakes, Control devices, Cabs, Electrical equipment, Electrical safety, Electrical protection equipment, Electric cables, Hydraulic equipment, Pneumatic equipment, Lifting, Occupational safety, Safe working load, Performance testing, Dynamic testing, Overturning, Mechanical testing, Testing conditions, Legislation